Dental caries experience and periodontal health status in a sample of autism children - Hussein, Fighan Jalal; Mustafa, Alaa Mahmud; Sabir, Sazgar Muhammed (Zanco Journal of Medical Sciences (ZJMS), 2018)
Background and Objective: Autism is a persistent neurodevelopmental condition. This study aimed to investigate carious and periodontal problems among a sample of children with autism in Erbil, Iraq. Methods: A total of 44 autistic children aged 1-14 years (30 males and 14 females) attending Erbil, Iraq Autism Centers were enrolled in the study. The control group consisted of 44 non-autistic children chosen from different schools which represent different geographical locations in Erbil city in the period between September, 1st 2014 to January, 1st 2015 to have matched age, sex and socioeconomic status. Each patient received an assessment of caries prevalence. Other conditions assessed were oral hygiene and gingival health status. The t-test of significance was used to compare groups. Results: Data analyzed for the present study comprised observations from a group of children (cases = 44) diagnosed with autism matched with healthy children (controls = 44). The autistic children had lower decayed, missing or filled teeth than unaffected children with nonsignificant differences. The mean decayed-missing-filled teeth in primary teeth (dmft) of the autistic group was 11.57 ± 11.41 while that of the controls was 15.36 ± 12.81. The mean Decayed-Missing-Filled teeth in permanent teeth (DMFT) of the autistic group was 2.36 ± 3.86 and 2.89 ± 3.78 in the controls. With advancing age, the value of decayed, missing and filled teeth increased. Almost all of the autistic children had fair oral hygiene (1.291 ± 0.89) and had gingivitis. Conclusion: Autistic children displayed lower dmft, DMFT scores compared to control group, fair oral hygiene level, and had gingivitis than did the unaffected control children. Hence, non-autistic children need further consideration.